Experimental Research and Numerical Simulation of Wing Boxes under Pure Bending Load. (23rd July 2014) - Wang, Peiyan; Yao, Shile; Wang, Xinmei; Yue, Zhufeng
Abstract : Two full-scale wing boxes with different types of butt joints were investigated under pure bending load, and numerical methods, including global analysis and detailed analysis, were proposed to determine the reasons for failure of the wing boxes. Wing boxes were tested under bending loads applied by a multichannel force control system. The experimental results showed that the region of the butt joint was the weakest location of the wing boxes, and the damage loads were far less than the design load. The global analysis and detailed analysis were carried out on the wing boxes, focusing on the region of the butt joint, to determine the reasons for failure. Global analysis in explicit dynamic modulus was adopted to simulate the loading process of the two wing boxes. Meanwhile, detailed finite element models created in Patran/Nastran were used to evaluate the stability. Comparing experimental results with numerical counterparts, it is shown that the failure of the wing boxes is induced by local buckling occurring around the butt joint. In addition, the wing box that uses butt joints with lap jointed sheets is more rigid than that without lap jointed sheets, and the stress distribution is more uniform. The numerical analysis proposed by the paper can help with structure design in preliminary assessment.